The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1111/all.15029
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a safe monoclonal anti‐human IL‐2 that is effective in a murine model of food allergy and asthma

Abstract: Background: Regulatory T cells (Tregs) are known to protect against allergies.Moreover, the decrease in the frequency and efficiency of Tregs amplifies allergic symptoms.Aim: This study investigated whether expanding Tregs in vivo with an IL-2/IL-2 antibody complex could be safe, well tolerated and efficient in a therapeutic setting in allergies. Methods:We produced an anti-IL-2 antibody (1C6) and demonstrated that when it is complexed to human IL-2, it increases IL-2 efficiency to induce Tregs in vivo without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
(111 reference statements)
0
4
0
Order By: Relevance
“…In both models, the suppressive function of Treg could further be enhanced by the CD4-binding HIV-1 surface protein gp120, preventing GvHD or allergic airway inflammation, respectively (79,80). Recently, it has been reported that low-dose IL-2 or a combination of IL-2/anti-IL-2 restored Treg numbers and function in respiratory and food allergies, thereby improving allergic markers and symptoms (81)(82)(83). Manipulation of the intestinal microbiota associated with induction or expansion of Treg cells as shown in numerous animal models of allergy and asthma may also offer novel strategies for immunomodulation of food allergies.…”
Section: Current Therapeutic Applications In Allergic Diseases: I Ind...mentioning
confidence: 99%
“…In both models, the suppressive function of Treg could further be enhanced by the CD4-binding HIV-1 surface protein gp120, preventing GvHD or allergic airway inflammation, respectively (79,80). Recently, it has been reported that low-dose IL-2 or a combination of IL-2/anti-IL-2 restored Treg numbers and function in respiratory and food allergies, thereby improving allergic markers and symptoms (81)(82)(83). Manipulation of the intestinal microbiota associated with induction or expansion of Treg cells as shown in numerous animal models of allergy and asthma may also offer novel strategies for immunomodulation of food allergies.…”
Section: Current Therapeutic Applications In Allergic Diseases: I Ind...mentioning
confidence: 99%
“…1 ). In preclinical models, IL-2C-expanded Tregs not only protected from experimental autoimmune encephalitis and prolonged survival of allogeneic islet grafts [ 45 ] but also ameliorated allergen-induced airway hyperreactivity in prophylactic and therapeutic settings, where they reduced allergen-specific IgE serum levels [ 46 , 47 ] and expanded Treg during sublingual immunotherapy [ 48 ] and food allergy, respectively [ 49 ]. Moreover, it was shown that IL-2C-expanded Treg cells could be recalled upon allergen challenge, which was associated with suppression of lung-specific Th2 responses long after initial treatment [ 50 ].…”
Section: Distinct Monoclonal Antibodies Shape the Function And Increa...mentioning
confidence: 99%
“…Treg cells are a subtype of T cells that maintain immune function and regulate immune adaptation. [177][178][179][180] The expression of Treg cells is closely related to the pathological state of the respiratory tract, and its functional impairment can potentially lead to autoimmune diseases. The increase of HIF-1α and HIF-2α in hypoxic conditions can inhibit the differentiation of Treg cells.…”
Section: Effect Of Hypoxia On T Cellsmentioning
confidence: 99%